Surkhan State Reserve Main Problems and Principles of Nature Protection - Tuxtaev Baratali Mustofoqul O’g’li (Indonesian Journal of Innovation Studies, 2022)
Surkhan state reserve main problems and principles of nature protection. the current state of the reserve The biodiversity of the protected area, flora and fauna were considered and the current problems of the reserve and their solutions were considered.